Comparison of Process Signatures for thermally dominated processes. (November 2021) - Karpuschewski, B.; Lübben, Th.; Meinke, M.; Eckert, S.; Frerichs, F.; Schneider, S.; Klink, A.; Langenhorst, L.; Sölter, J.
Abstract: Four machining processes are analyzed with respect to the internal material loads and modifications in the surface layer. The processes considered are grind hardening, induction hardening, laser hardening as well as Electrical Discharge Machining (EDM), which all impose primarily heat loads on the workpiece. The concept of Process Signatures is assumed, in which suitable descriptive quantities of the internal material loads are correlated to the resulting modifications in the surface layer. The surface layer modifications chosen here are the residual stresses, phase compositions and the thickness of the transformation zone. Validated numerical simulation methods are used to determine the material modifications for grind hardening and induction hardening. For laser hardening probe measurements are used for the residual stresses and the thickness of the transformation zone. For the EDM the residual stresses were also measured. The thickness of the white layer and the transformation zone were derived from simulations. In all cases, numerical simulations are conducted to determine the temperature field during the machining process. The analysis of the involved mechanisms such as martensite formation suggests that the maximum temperature gradient is a suitable descriptive quantity for the generation of residual stresses. The results obtained for the four machining processes confirm this behavior. The depth of the transformed zone is shown to correlate with the square of the maximum temperature multiplied by the square root of the contact time. Although the different processes investigated show several orders of magnitude different heating and cooling rates, the results achieved are promising and confirm the applicability of the Process Signature concept.